2023
DOI: 10.1371/journal.pone.0286409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speed and leading or trailing limbs on surface muscle activities during canter in Thoroughbred horses

Abstract: Given that Thoroughbred horses’ canter is an asymmetric gait, not only speed but also leading or trailing limbs could affect muscle activities. However, the muscle activity during a canter remains poorly understood. Hence, we aimed to investigate speed and lead-side (leading or trailing) effects on surface electromyography (sEMG) during a canter. The sEMG data were recorded from left Musculus brachiocephalicus (Br), M. infraspinatus (Inf), long head of M. triceps brachii (TB), M. gluteus medius (GM), M. semite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(55 reference statements)
0
2
1
Order By: Relevance
“…Our results in TB align with these findings. We observed that the normalized iEMG values during the swing phase on an 8% grade significantly increased compared to a 0% grade, indicating that TB may play an important role in decelerating the forelimb [36]. Contrary to Hodson-Tole's findings [20], the activity of Br was not affected by grade in our study.…”
Section: Plos Onecontrasting
confidence: 90%
See 2 more Smart Citations
“…Our results in TB align with these findings. We observed that the normalized iEMG values during the swing phase on an 8% grade significantly increased compared to a 0% grade, indicating that TB may play an important role in decelerating the forelimb [36]. Contrary to Hodson-Tole's findings [20], the activity of Br was not affected by grade in our study.…”
Section: Plos Onecontrasting
confidence: 90%
“…These muscles may play an important role in decelerating the limb and redirecting it from protraction to retraction in the late swing phase. This function is similar to the role of the long head of TB, where a shorter swing duration necessitates faster limb protraction [35,36]. This indicates that not only passive properties, such as the biceps brachii tendon unit's catapult mechanism, but also an increase in muscle activity, could facilitate faster limb movements on an uphill grade [10,37].…”
Section: Plos Onementioning
confidence: 64%
See 1 more Smart Citation